Fabrication of a Greener TiO2@Gum Arabic-Carbon Paste Electrode for the Electrochemical Detection of Pb2+ Ions in Plastic Toys - Sivan, Saranya Kothaplamoottil; Shankar, Sarojini Sharath; N, Sajina; Kandambath Padinjareveetil, Akshaykumar; Pilankatta, Rajendra; Kumar, V B Sameer; Mathew, Beena; George, Bini; Makvandi, Pooyan; Černík, Miroslav; Padil, Vinod V T; Varma, Rajender S (ACS omega, 2020)
A novel greener methodology is reported for the synthesis of titanium dioxide (TiO2) nanoparticles (NPs) using gum Arabic (Acacia senegal) and the characterization of the ensuing TiO2 NPs by various techniques such as X-ray diffraction (XRD), Fourier transform infrared, Raman spectroscopy, scanning electron microscopy-energy dispersive X-ray, transmission electron microscopy (TEM), high resolution-TEM, and UV-visible spectroscopy. The XRD analysis confirmed the formation of TiO2 NPs in the anatase phase with high crystal purity, while TEM confirmed the size to be 8.9 ± 1.5 nm with a spherical morphology. The electrode for the electrochemical detection of Pb2+ ions was modified by a carbon paste fabricated using the synthesized TiO2 NPs. Compared to the bare electrode, the fabricated electrode exhibited improved electro-catalytic activity toward the reduction of Pb2+ ions. The detection limit, quantification limit, and the sensitivity of the developed electrode were observed by using differential pulse voltammetry to be 506 ppb, 1.68 ppm, and 0.52 ± 0.01 μA μM-1, respectively. The constructed electrode was tested for the detection of lead content in plastic toys.